Corporate Governance Mechanisms and Dividend Policy: The Moderating Role of Disclosure Quality - Agustinus Winoto; Naila Erum (GOVERNORS, 2026)
This study is to investigate corporate governance mechanisms, specifically audit firm size, audit duration, and managerial ownership, as well as dividend policy, with the disclosure quality serving as a moderating factor. For the years 2020 to 2024, about 65 companies data were obtained from the financial statements of trading companies that were listed on the Indonesia Stock Exchange (IDX). Audits were performed on each and every one of the utilized financial statements. The information was collected through the use of purposive sampling, and it was then processed using SPSS. Using Fixed Effect Model, while the other criteria did not have any significant link with dividend policy, the data suggested that the size of the audit business did have a positive and large correlation with dividend policy. The outcomes of the moderation analysis indicated that the quality of the disclosure was substantial and had the potential to improve upon earlier findings.